Exploring Figurative Language: Expressions and Metaphors in Sports Reporting of Java Pos (Edition, June 1, 2018) - Mas’ud Muhammadiah; Roma Wijaya; Achmad Naufal Irsyadi; Muh. Hasyim Rosyidi; Zarkasi (RETORIKA: Jurnal Ilmu Bahasa, 2023)
The utilization of figurative language in sports reporting significantly enhances communication’s allure and competitiveness within this realm. Figurative language entails expressions not meant to be taken literally but carrying implied meanings that enrich interpretation for readers or listeners. It crucially illustrates action and drama in sports news, engendering a more immersive reading experience and influencing how events are comprehended. This research probes into the use of figurative language, particularly expressions and metaphors, within sports reporting's context. The study’s focal point was the June 1, 2018 edition of the esteemed Indonesian newspaper, Java Pos, renowned for its vibrant sports reporting, particularly in football. Data consisted of expressions and metaphors in the form of verbs, nouns, adjectives, and numerals, sourced from Java Pos' sports reporting (June 1, 2018 edition), especially relating to football. The methodology involved participatory observation reading 7 football-specific sports pieces and scrutinizing each for expressions and metaphors. Additionally, documentation was employed collecting and analyzing articles from the designated edition to assess metaphors and expressions through a figurative language lens. Post data collection, data was condensed and classified by category (nouns, verbs, adjectives, and numerals) then verified and interpreted contextually. Content analysis was applied for data analysis, comprehending the contextual use and its impact on reader comprehension. The findings unveiled the presence of expressions and metaphors, encompassing verb phrases, nouns, adjectives, and numerals, in the news reports. This study uncovers the usage of figurative language, enriching communication, fostering creativity, and contributing to elevated sports reporting quality and deeper audience understanding.